Overview Of Online Game Addiction In Stikes Santa Elisabeth Medan Students In 2021 - Lucia Cindi Situmorang (Jurnal EduHealth, 2022)
Background :Science and technology today is growing rapidly, one of which is in the form of online games, the more often a person plays it can become addicted and in early adulthood emotional responses often avoid problems by playing online games.Method: The research method used isdescriptive.Results: research results obtainedshows that the respondents are in the category of severe addiction as many as 63 respondents (73.3 %), moderate addiction 17 respondents (19.8%), and mild addiction 5 respondents (5.9%). If addiction is not handled properly, it can lead to self-control because it is not able to reduce play time so that social relationships and tasks become hampered.Discussion: Respondents feel that playing online games is only to fill spare time, relieve stress, begin to be able to determine activities that must be prioritized and be able to control themselves.